Breast Cancer Survival in Multiple Sclerosis: A Matched Cohort Study. (6th July 2021) - Marrie, Ruth Ann; Maxwell, Colleen; Mahar, Alyson; Ekuma, Okechukwu; McClintock, Chad; Seitz, Dallas; Groome, Patti
Abstract : Objective: To test the hypotheses that overall survival and cancer-specific survival after breast cancer diagnosis would be lower in persons with multiple sclerosis (MS) as compared to persons without MS using a retrospective matched cohort design. Methods: We applied a validated case definition to population-based administrative data in Manitoba and Ontario, Canada, to identify women with MS. We linked the MS cohorts to cancer registries to identify women with breast cancer. Then we selected 4 breast cancer controls without MS matched on birth year, cancer diagnosis year, and region. We compared all-cause survival between cohorts using Cox proportional hazards regression adjusting for age at cancer diagnosis, cancer diagnosis period, income quintile, region, and Elixhauser comorbidity score. We compared cancer-specific survival between cohorts using a multivariable cause-specific hazards model. We pooled findings between provinces using meta-analysis. Results: We included 779 patients with MS and 3, 116 controls with breast cancer. Most patients with stage data (1, 976/2, 822 [70.0%]) were diagnosed with stage I or II breast cancer and the mean (SD) age at diagnosis was 57.8 (10.7) years. After adjustment for covariates, MS was associated with a 28% increased hazard for all-cause mortality (hazard ratio [HR] 1.28; 95% confidence interval [CI] 1.08–1.53), but was not associated with altered cancer-specific survival (HR 0.98; 95% CI 0.65–1.46). Conclusion: Women with MS have lower all-cause survival after breast cancer diagnosis than women without MS. Future studies should confirm these findings in other populations and identify MS-specific factors associated with worse prognosis.